DRES-07. DEFINING THE MECHANISMS OF ACQUIRED RESISTANCE TO TYROSINE KINASE INHIBITORS IN EGFR-DRIVEN GLIOBLASTOMAS USING INTEGRATED KINOME AND TRANSCRIPTOME PROFILING. (5th November 2018) - Shelton, Abigail; Smithberger, Erin; Butler, Madison; Flores, Alex; Bash, Ryan; Angus, Steven; Sciaky, Noah; Dhruv, Harshil; Johnson, Gary; Berens, Michael; Furnari, Frank; Miller, Ryan
Abstract: Glioblastoma (GBM), the most common and malignant adult primary brain tumor, has been extensively molecularly characterized. Two mutations occur at particularly high frequency: CDKN2A deletion (50–60%) and EGFR (40–50%), especially EGFRvIII (~35%) in which exons 2–7 are deleted and result in constitutive kinase activation. EGFR is the most attractive therapeutic target due to frequent activating mutations and ready availability of multiple targeted inhibitors. Several EGFR-targeted tyrosine kinase inhibitors (TKI) have failed clinically, due in part to intrinsic and acquired resistance. To examine these mechanisms, we are using genetically-engineered mouse astrocytes harboring homozygous deletions of Cdkn2a, as well as the activating EGFRvIII mutation (CEv3). To model acquired resistance, CEv3 astrocytes were made intrinsically resistant to the EGFR TKI gefitinib or erlotinib via long-term exposure, both in vitro and in vivo . We found that long-term gefitinib or erlotinib exposure confers variable levels of cross resistance to a panel of second- and third-generation EGFR-TKI (ΔIC50 1.12-36.1-fold), relative to non-resistant parent lines. We have previously shown that dynamic kinome reprogramming may be responsible for TKI resistance. Therefore, we are using a chemical proteomics method, multiplexed inhibitor beads and mass spectrometry (MIB-MS), to examine changes in the expressed and functional kinome, in both the presence or absence of one of several EGFR-TKI known to penetrate the blood-brain barrier. Additionally, we are performing RNA sequencing (RNA-seq) to inspect transcriptomic alterations in response to these drugs. Preliminary RNA-seq results showed that resistant CEv3 mouse astrocytes clustered separately from their non-resistant in vitro and in vivo counterparts. Together, data from these experiments will create a framework of transcriptomic and proteomic changes that occur in murine models of GBM with defined mutational profiles. This framework can then be used to help define novel therapeutic targets that could significantly alter the current treatment paradigm of GBM.